Co-gestion public-privé de l’activité minière : quel développement local dans la « province modèle » de San Juan (Argentine) ? - Mathilde Denoël; Martine Guibert (Caravelle)
The Argentine province of San Juan is considered as an emblematic case given that the authorities’ speech underlines its character of “mining model province”. By analysing the reconfiguration of public and private agents’ system as well as the power relationships which develop in various scales, it seems that the local socio-spatial translations of the relations of dependence thus woven are the expression of political choices linked to the mining activity and the fragility of the model.